Enhancing Proctological Outcomes: The Role of Hyaluronic Acid in Hemorrhoid Care – An Innovative Adjunct to Surgery - Upadhyay, Riddhi; Vadaliya, Akshat; Pathak, Haryax V.; Upadhyay, Soham (Journal of Coloproctology, 2025)
Hemorrhoids are common anorectal conditions characterized by swollen and inflamed veins in the rectal and anal regions. They are classified as internal, external, or mixed, and may present with rectal bleeding, pain, itching, and prolapse. Chronic constipation, prolonged straining, and increased intra-abdominal pressure are frequent etiological factors. Management strategies range from conservative measures, such as dietary modifications and topical agents, to surgical procedures including hemorrhoidectomy and stapled hemorrhoidopexy.To describe the therapeutic potential of hyaluronic acid (HA) in the management of hemorrhoids and to report clinical outcomes in patients treated with HA infiltration.Five patients with hemorrhoids underwent HA infiltration. Treatment was associated with significant symptom relief, reduced edema, and improved post-surgical recovery. The mechanism of action involved enhanced fibroblast activity, decreased inflammatory cytokines, and improved mucosal hydration.Hyaluronic acid demonstrates promising results as a safe and effective option for hemorrhoid management. Its hydrating, anti-inflammatory, and wound-healing properties support its role as a versatile therapeutic agent in both conservative and surgical settings, contributing to improved patient outcomes.
Keywords: hemorrhoids; hemorrhoidectomy; hyaluronic acid; proctology